2009
DOI: 10.1080/15228830902749039
|View full text |Cite
|
Sign up to set email alerts
|

Child Welfare Workers' Adoption of Decision Support Technology

Abstract: Child welfare workers must process complex information in deciding to refer clients to appropriate mental health services. Decision support systems (DSS) have been demonstrated in other fields to be an important tool, yet little research has been done in child welfare. This study focused on the adoption of a specific DSS into child welfare practice. Quantitative analysis was used to demonstrate the diffusion of innovation process among a sample of state child welfare workers, while qualitative analysis was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Rohrbach et al 33 found that the training of the school principal, but not the intensity of teacher training, increased the likelihood of adoption of a school-based intervention. Foster and Stiffman 34 found that the addition of a personal digital assistant version of a desktop decision support system for social service workers increased EBP use. Epstein et al found that (1) providing pre-packaged medications to enable practitioners to conduct n of 1 double-blind placebo-controlled trials of different stimulant doses for use with individual patients, along with (2) specialist support for its interpretation to pediatric practices increased the use of such trials, though it did not increase the frequency of monitoring of ADHD symptoms over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rohrbach et al 33 found that the training of the school principal, but not the intensity of teacher training, increased the likelihood of adoption of a school-based intervention. Foster and Stiffman 34 found that the addition of a personal digital assistant version of a desktop decision support system for social service workers increased EBP use. Epstein et al found that (1) providing pre-packaged medications to enable practitioners to conduct n of 1 double-blind placebo-controlled trials of different stimulant doses for use with individual patients, along with (2) specialist support for its interpretation to pediatric practices increased the use of such trials, though it did not increase the frequency of monitoring of ADHD symptoms over time.…”
Section: Resultsmentioning
confidence: 99%
“…Aarons et al 37 found that fidelity monitoring resulted in lower levels of staff emotional exhaustion when such monitoring took place in the context of sustainment of an EBP (in this case SafeCare) compared to fidelity monitoring for providers providing usual care services. In their small clinical trial comparing desktop computer only versus desktop computer plus personal digital assistant access to the a decision making support system, Foster and Stiffman 34 found that use of the system declined during the sustainment phase of their trial, though use of the decision support system remained higher in the desktop computer plus personal digital assistant condition during the sustainment phase.…”
Section: Resultsmentioning
confidence: 99%
“…() explored the potential of what they refer to as ‘artificial intelligence’ to develop ‘expert systems’ to support professional decision‐making. Research‐based development of DSS continued in the 21 st century and identified particular challenges in their design and implementation such as making them useful in the contexts in which they are implemented (Fitch, , ; Foster and Stiffman, ), getting practitioners to use them (Fitch, , ; Foster and Stiffman, ) and accounting for the importance of emotion and bias in human decision‐making (MacFadden and Schoech, ).…”
mentioning
confidence: 99%
“…Other factors not included in this study may influence assessment, referral practices and service provision for youth. Studies conducted with the St. Louis Children’s Division (Fedoravicius, McMillen, Rowe, Kagotho & Ware, 2008; Foster & Stiffman, 2009; McMillen, Fedoravicius, Rowe, Zima & Ware, 2007) show that mental health services for youth in the child welfare system are frequently court ordered. The pressure to comply with court demands for documentation and time constraints influence workers’ assessment and referral practices (Fedoravicius et al, 2008; Foster & Stiffman, 2009; Smith & Donovan, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…If training, experience and education were not associated with connectivity, other factors that were not included in these analyses must be important. Focus groups revealed that interactions at the office shaped workers’ familiarity with other providers and their referral patterns (Foster & Stiffman, 2009). Constructive organizational culture and positive perceptions of organizational climate influence work-place interactions and may have a role in the transfer of practice knowledge (Glisson & Green, 2006; Uzzi & Lancaster, 2003).…”
Section: Discussionmentioning
confidence: 99%